Fusidic acid betamethasone lipid cream. (May 2016) - Girolomoni, G.; Mattina, R.; Manfredini, S.; Vertuani, S.; Fabrizi, G.
Summary: Bacterial infections of the skin and soft tissues are frequent disorders. They can be primitive infections (e.g. impetigo, folliculitis) or secondary infections complicating other diseases, particularly atopic dermatitis. The most common aetiologic agent is Staphylococcus aureus . Topical antibiotic therapy may be sufficient in many instances to control these infections. Fusidic acid is an antibiotic used topically on the skin which is very active against S. aureus, including methicillin‐resistant strains, and other Gram‐positive bacteria. Resistance rates to fusidic acid are stably low. A fusidic acid and betamethasone formulation in a lipid‐enriched cream (lipid cream) has been recently developed in order to provide effective antibacterial and anti‐inflammatory activities in conjunction with a powerful emollient and moisturising effect. This preparation may be especially useful in patients with atopic‐infected eczema.